PENGEMBANGAN E-MODUL PERUBAHAN LINGKUNGAN BERBASIS PROBLEM BASED LEARNING SEBAGAI BAHAN AJAR SISWA KELAS X SMA - Rohmah, Mangzilatur; Sholihah, Mar'atus; Malahayati, Eva Nurul (BIOEDUKASI (Jurnal Pendidikan Biologi), 2025)
This research aims to develop an environmental change e-module based on problem based learning that is feasible and practical. This research uses a research and development (R&D) model with Sugiyono's development design which is limited to stage 7. The product trial subjects were 21 class XI G students at SMAN 4 Blitar City and 1 Biology teacher at SMAN 4 Blitar City. The data collection instruments used included expert validation questionnaires, and student and teacher readability questionnaires. The results of the development research show that problembased learning based e-modules are feasible and practical as shown by 1) product feasibility consisting of material validation of 87.85%, language validation of 85%, and learning validation of 93.75% with the very feasible category 2) product practicality with a student readability test of 93.69% and a teacher readability test of 96% in the very practical category.